Conjugacy of CNA pulsations and their source movement in the auroral zones - Shibuya, Senkichi; Higuchi, Yoshihiro; Sato, Natsuo; Maezawa, Kiyoshi (National Institute of Polar Research, 1991)
P(論文) A statistical character of seasonal variation for the conjugacy of quasi periodic cosmic radio noise absorption (called CNA pulsation) is studied with the chart paper measured at Syowa Station in Antarctica and its magnetically conjugate Husafell Station in Iceland. On the basis of the analyses of relative phase difference of the CNA pulsation for two cases among three stations in Iceland, the direction of source movement is also studied. The results indicate that the sources of CNA pulsation of Pc 3 and Pc 5 range in the prenoon sector moved generally from north (or high latitude) to south (or low latitude) direction, and from east to west direction, while the source of CNA pulsation at Pc 5 range in the morning sector moved primarily from south to north direction, and from east to west direction. departmental bulletin paper